Rabies control via co-creation: A model for sustainable one health interventions - Bor, Nicholas; Njenga, Geoffrey; Slater, Annabel; Munywoki, Peterkin; Chepyatich, Dorcas; Owino, D.; Murungi, Maurice K.; Muloi, Dishon M.; Thomas, Lian F. (2025)
Rabies is a fatal zoonotic disease that can be effectively controlled by vaccinating 70% of at-risk dog populations. Rabies is a persistent health threat in Kenya due to low rabies vaccination coverage and low awareness among dog owners. In 2014, the Zoonotic Disease Unit launched the national rabies elimination strategy and listed Machakos County as one of the pilot counties due to the high rabies burden. Between 2021 and 2024, the International Livestock Research Institute, Veterinarians Sans Frontiers - Germany and Machakos County government implemented a series of free mass dog rabies vaccination campaigns. To support vaccine uptake, the research team co-created contextual rabies sensitization materials and vaccination announcement posters with the community. This was achieved through a series of key informant interviews, focus group discussions and co-creation workshops with community members who presented their dogs for vaccination and agreed to be part of these activities. Community members shared that dogs play both tangible and intangible roles in their lives. The main tangible roles included guarding homes, livestock, and crops. Friendship was highlighted as the most important intangible role. They stressed that a bond of friendship must first be established for dogs to serve their owners meaningfully. They shared that the co-creation process deepened their understanding of rabies and helped them better appreciate the value of their dogs. As a result, they recognized the importance of vaccinating their dogs — their friends — against the disease. Co-creating public health solutions with communities is an invaluable approach to raising awareness, building trust, and boosting participation in campaigns, all of which are vital for long-term sustainability. We advocate for greater use of co-creation processes, especially as we apply the One Health approach to address zoonotic threats and other health challenges.